Validating a TPCK-S Instrument for Hologram-Based Mathematics Teaching - Kaharuddin, Andi; García García, Javier; Magfirah, Irma; Yulismayanti, Yulismayanti (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
The successful use of 3D holograms in teaching geometry depends greatly on teachers’ practical skills. However, there remains a substantial gap in understanding how these skills are developed and how they can be reliably assessed. This study, carried out with mathematics teachers in Southeast Sulawesi, Indonesia, seeks to address this issue by (1) proposing a theoretical model for the development of Technological Pedagogical Content Knowledge and Skills (TPCK-S), and (2) creating and validating an instrument to measure this construct. Following a sequential exploratory mixed-methods design, a theoretical model was first built through a grounded theory study with six junior high school mathematics teachers. Building on this model, an instrument was then empirically validated with a sample of 112 junior high school teachers through the combined use of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The findings revealed a three-stage TPCK-S development model consisting of Technical Familiarization, Pedagogical Experimentation, and Fluent Integration. In addition, the validated 28-item instrument demonstrated a solid four-factor structure, with confirmatory factor analysis (CFA) showing good model fit and internal consistency reliability reaching an excellent level (α = 0.91). Overall, this study contributes a rigorously tested TPCK-S instrument that can serve as a valuable diagnostic tool to support and strengthen teacher professional development in the digital era.